2020
DOI: 10.3390/antiox9050415
|View full text |Cite
|
Sign up to set email alerts
|

Antirhea borbonica Aqueous Extract Protects Albumin and Erythrocytes from Glycoxidative Damages

Abstract: Diabetes constitutes a major health problem associated with severe complications. In hyperglycemic conditions, chronically increased oxidation and glycation of circulating components lead to advanced glycation end-products (AGEs) formation, a key contributor in diabetes complication progression. In line with literature documenting the beneficial properties of herbal teas, this study evaluates the antioxidant/glycant properties of Antirhea borbonica (Ab). Ab aqueous extract effects were tested on human albumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
0
18
0
2
Order By: Relevance
“…It is important to note that PRE exert high protective effects at 25 µM by increasing the HT50 from 8.01 ± 0.16 h (for H. ambavilla ) to 11.72 ± 0.12 h (for D. viscosa ). As previously reported, polyphenols may prevent hemolysis and thus increase red blood cell half-life [ 24 , 26 ]. As presented in Figure 4 , at a final concentration of 25 µM GAE, half-hemolysis time was prolonged from 2.9 ± 0.2 h to 6.9 ± 0.1 h for the infusions, from 2.3 ± 0.2 h to 5.8 ± 0.1 h for the decoctions and from 1.5 ± 0.2 h to 5.2 ± 0.1 h for the PRE.…”
Section: Impact Of Infusion and Decoction Process On The Antioxidamentioning
confidence: 82%
See 1 more Smart Citation
“…It is important to note that PRE exert high protective effects at 25 µM by increasing the HT50 from 8.01 ± 0.16 h (for H. ambavilla ) to 11.72 ± 0.12 h (for D. viscosa ). As previously reported, polyphenols may prevent hemolysis and thus increase red blood cell half-life [ 24 , 26 ]. As presented in Figure 4 , at a final concentration of 25 µM GAE, half-hemolysis time was prolonged from 2.9 ± 0.2 h to 6.9 ± 0.1 h for the infusions, from 2.3 ± 0.2 h to 5.8 ± 0.1 h for the decoctions and from 1.5 ± 0.2 h to 5.2 ± 0.1 h for the PRE.…”
Section: Impact Of Infusion and Decoction Process On The Antioxidamentioning
confidence: 82%
“…Several reports emphasize on the use of medicinal plants and polyphenols to prevent oxidative stress damage notably in red blood cells [ 24 , 51 , 52 , 53 , 54 ]. Oxidative stress affects membrane stability and fluidity [ 55 ].…”
Section: Impact Of Infusion and Decoction Process On The Antioxidamentioning
confidence: 99%
“…The most traditionally employed method for preparation of herbal remedies is infusion, which consists of soaking the plant part in very hot water [ 50 ]. Recently, A. borbonica plant infusion was shown to exert antioxidant properties on in vitro and in vivo models exposed to glycoxidative condition [ 90 ]. It will be of interest to evaluate the benefits of infusions that were prepared from the medicinal plants tested here, during cerebrovascular complications related to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Antirhea borbonica ( A. borbonica ) leaves are peculiarly interesting, as they are widely used in traditional medicine for treating, among others, diabetes, urinary tract infection, diarrhea, hemorrhage, rheumatism and also kidney stones [ 26 , 27 ]. Our laboratory has shown that A. borbonica exhibited strong antioxidant and anti-inflammatory effects, in vitro, on preadipocytes, cerebral endothelial cells and red blood cells [ 22 , 28 , 29 ]. Those antioxidant and anti-inflammatory biological effects were mainly associated with the capacity of polyphenols to down-regulate on one hand key molecular targets such as IL6, MCP-1 and NF-kB, and on the other hand increase superoxide dismutase (SOD) as well as the redox-sensitive translational factor Nrf2.…”
Section: Introductionmentioning
confidence: 99%
“…Those antioxidant and anti-inflammatory biological effects were mainly associated with the capacity of polyphenols to down-regulate on one hand key molecular targets such as IL6, MCP-1 and NF-kB, and on the other hand increase superoxide dismutase (SOD) as well as the redox-sensitive translational factor Nrf2. In addition, the in vitro studies showed that predominant polyphenols such as quercetin, chlorogenic and caffeic acids were able to reduce free radicals through DPPH and AAPH radical-scavenging tests [ 22 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%